The problems of translating Virgil's Aeneid in A.A. Fet's letters to D.I. Naguewskii - Алмазова Н. (Київський національний університет імені Тараса Шевченка, 2012)
The article discusses the views of the Russian poet of the 19th century Afanasy Fet on translating the Classical writings, among them Virgil's Aeneid, as seen in his letters to Prof. Darius Naguewski of the Kazan' University.

В статье рассматриваются взгляды А.А. Фета на перевод произведений древних авторов, в частности "Энеиды" Вергилия, в письмах профессору Казанского университета Д.И. Нагуевскому.
Проблемы перевода "Энеиды" Вергилия в письмах А.А. Фета Д.И. Нагуевскому